Informasi Sistem Keselamatan di Objek Wisata Nimo Highland Pangalengan Bandung - Heykal, Muhammad; Suesilowati, Suesilowati (CV. Creative Tugu Pena, 2024)
Occupational Health and Safety (K3) is a crucial aspect in every work environment, including tourism. Moreover, tourist destinations are included in natural tourism, of course the health and safety of visitors must be taken into account. One of these tourist destinations is NiMo Highland. NiMo Highland is a tourist destination in the Pangalengan area, Bandung. This tour pampers tourists with very beautiful views of mountains and lakes. Apart from that, tourists can also walk on the bridge over the tea gardens and mountains which are very beautiful with a refreshing breeze. Since it opened, NiMo Highland has been immediately visited by visitors, not only from the surrounding community, but also from outside Bandung, so the number of visitors continues to increase every year. Based on this, it is very important to pay attention to Health and Safety. By using research methods in the form of direct visits and conducting interviews with 3 sources, from managers, supervisors to workers there, the results showed that NiMo Highland Management has tried to always maintain K3. Apart from that, there was a lot of evidence found in the form of signs, announcements using toa or speakers and security from the employees there. Seeing this, of course this is very good and really needs to be developed so that the contribution to K3 of visitors and employees will be maintained. Keywords: Safety System, Tourism, Occupational Health and Safety